Increased utilization of constraint in total knee arthroplasty following anterior cruciate ligament and multiligament knee reconstruction. (July 2019) - James, E. W.; Blevins, J. L.; Gausden, E. B.; Turcan, S.; Denova, T. A.; Satalich, J. R.; Ranawat, Amar S.; Warren, R. F.; Ranawat, Anil S.
Abstract : Aims: Anterior cruciate ligament (ACL) and multiligament knee (MLK) injuries increase the risk of development of knee osteoarthritis and eventual need for total knee arthroplasty (TKA). There are limited data regarding implant use and outcomes in these patients. The aim of this study was to compare the use of constrained implants and outcomes among patients undergoing TKA with a history of prior knee ligament reconstruction (PKLR) versus a matched cohort of patients undergoing TKA with no history of PKLR. Patients and Methods: Patients with a history of ACL or MLK reconstruction who underwent TKA between 2007 and 2017 were identified in a single-institution registry. There were 223 patients who met inclusion criteria (188 ACL reconstruction patients, 35 MLK reconstruction patients). A matched cohort, also of 223 patients, was identified based on patient age, body mass index (BMI), sex, and year of surgery. There were 144 male patients and 79 female patients in both cohorts. Mean age at the time of TKA was 57.2 years (31 to 88). Mean BMI was 29.7 kg/m 2 (19.5 to 55.7). Results: There was a significantly higher use of constrained implants among patients with PKLR (76 of 223, 34.1%) compared with the control group (40 of 223, 17.9%; p < 0.001). Subgroup analysis showed a higher use of constrained implants among patients with prior MLK reconstruction (21 of 35, 60.0%) compared with ACL reconstruction (55 of 188, 29.3%; p < 0.001). Removal of hardware was performed in 69.5% of patients with PKLR. Mean operative time (p < 0.001) and tourniquet time (p < 0.001) were longer in patients with PKLR compared with controls. There were no significant differences in rates of deep vein thrombosis, pulmonary embolism, infection, transfusion, postoperative knee range of movement (ROM), or need for revision surgery. There was no significant difference in preoperative or postoperative Knee Injury and Osteoarthritis Outcome Score for Joint Replacement (KOOS, JR) scores between groups. Conclusion: Results of this study suggest a history of PKLR results in increased use of constrained implants but no difference in postoperative knee ROM, patient-reported outcomes, or incidence of revision surgery. Cite this article: Bone Joint J 2019;101-B(7 Supple C):77–83